Correspondencia entre H. P. Coats y Roberto H. Todd - Todd, Roberto H.; Coats, H. P. (My University, 1922)
Asuntos políticos
Keywords: Puerto Rico--Politics and government.; Puerto Rico--Política y gobierno.